A multi model ensemble based deep convolution neural network structure for detection of COVID19. (January 2022) - Deb, Sagar Deep; Jha, Rajib Kumar; Jha, Kamlesh; Tripathi, Prem S
Highlights: A DCNN structure is proposed for detection of COVID-19 from chest X-ray images. The DCNN structure comprises four pre-trained CNN networks. The ensemble structure proposed is also evaluated on a private Chest X-ray dataset. The performance is compared with other state-of-the-art architectures available. Abstract: The year 2020 will certainly be remembered for the COVID-19 outbreak. First reported in Wuhan city of China back in December 2019, the number of people getting affected by this contagious virus has grown exponentially. Given the population density of India, the implementation of the mantra of the test, track, and isolate is not obtaining satisfactory results. A shortage of testing kits and an increasing number of fresh cases encouraged us to come up with a model that can aid radiologists in detecting COVID19 using chest Xray images. In the proposed framework the low level features from the Chest X-ray images are extracted using an ensemble of four pre-trained Deep Convolutional Neural Network (DCNN) architectures, namely VGGNet, GoogleNet, DenseNet, and NASNet and later on are fed to a fully connected layer for classification. The proposed multi model ensemble architecture is validated on two publicly available datasets and one private dataset. We have shown that our multi model ensemble architecture performs better than single classifier. On the publicly available dataset we have obtained an accuracy of 88.98% for three class classification and for binary class classification we report an accuracy of 98.58%. Validating the performance on private dataset we obtained an accuracy of 93.48%. The source code and the dataset are made available in the github linkhttps://github.com/sagardeepdeb/ensemble-model-for-COVID-detection .